Drug–drug–gene interaction risk among opioid users in the U.S. Department of Veterans Affairs. Issue 12 (23rd December 2022) - Chanfreau-Coffinier, Catherine; Tuteja, Sony; Hull, Leland E.; MacDonald, Sally; Efimova, Olga; Bates, Jill; Voora, Deepak; Oslin, David W.; DuVall, Scott L.; Lynch, Julie A.
Abstract : Supplemental Digital Content is Available in the Text. Combining consideration of drug–gene interactions and drug–drug interactions may provide an enhanced precision medicine approach to improve the likelihood of successful pain management outcomes. Abstract: Response to analgesic therapy is influenced by several factors including genetics and drug–drug interactions. Pharmacogenetic (PGx) variants in the CYP2D6 gene modify response to opioids by altering drug metabolism. We sought to determine the potential impact of PGx testing on the care of Veterans with noncancer pain prescribed opioids metabolized by CYP2D6 (codeine, hydrocodone, or tramadol). A retrospective analysis was performed within the Veterans Health Administration evaluating prescription records for pain medications metabolized by CYP2D6 and interacting drugs from 2012 to 2017. Among 2, 436, 654 Veterans Health Administration pharmacy users with at least 1 opioid prescription, 34% met the definition of chronic use (longer than 90 days with more than 10 prescriptions or 120 days-supply). Opioids were commonly coprescribed with antidepressants interacting with CYP2D6 (28%). An estimated 21.6% (n = 526, 905) of these patients are at an elevated risk of an undesirable response to their opioid medication based on predicted phenotypes and drug–drug interactions: 3.5% are predicted CYP2D6 ultrarapid metabolizers and at increased risk for toxicity, 5.4% are poor metabolizers at higher risk for nonresponse, and 12.8% are normal or intermediate metabolizers coprescribed a CYP2D6 inhibitor leading to phenoconversion into poor metabolizer. Despite the high rate of coprescription of opioids and interacting drugs, CYP2D6 testing was infrequent in the sample (0.02%), and chart review suggests that test results were used to optimize antidepressant treatments rather than pain medications. Using PGx testing combined with consideration of phenoconversion may allow for an enhanced precision medicine approach to pain management in Veterans.